Застосування моделей NLP для оптимізації пошуку в файлових сховищах - Коваль, Г. К.; Гриньова, О. Є. (ХНУРЕ, 2025)
This research implements AI-powered search for file storage platforms using vector search and NLP models. The system analyzes and indexes documents, enabling semantic searches based on content and context. It uses Sentence Transformers for vector representations and Pinecone for efficient storage and retrieval. This innovation overcomes traditional search limitations, enhancing document management efficiency across various domains. The project aims to improve user productivity by providing more relevant search results and streamlining file retrieval processes in large-scale document repositories.
Keywords: модель NLP; файлові сховища